Building an Undergraduate Book Approval Plan for a Large Academic Library - Denise Koufogiannakis; Sandy Campbell; Fred Ziegler (Partnership: The Canadian Journal of Library and Information Practice and Research, 2007)
The University of Alberta Libraries (UAL), working with two book vendors,created large-scale undergraduate book approval plans to deliver newpublications. Detailed selections profiles were created for many subject areas,designed to deliver books that would have been obvious choices by subjectselectors. More than 5800 monographs were received through the book approvalplans during the pilot period. These volumes proved to be highly relevant tousers, showing twice as much circulation as other monographs acquired duringthe same time period. Goals achieved through this project include: release ofselectors’ time from routine work, systematic acquisition of a broadly based highdemandundergraduate collection and faster delivery of undergraduate materials.This successful program will be expanded and incorporated into UAL’s normalacquisitions processes for undergraduate materials.